2019
DOI: 10.1038/s41598-019-42117-w
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale ocean fronts act as biological hotspot for southern elephant seal

Abstract: The area west of the Kerguelen Islands (20–70°E/45–60°S) is characterized by a weak mesoscale activity except for a standing meander region of the Antarctic Circumpolar Current (ACC) localized between 20 and 40°E. A unique bio-physical dataset at high-resolution collected by a southern elephant seal ( Mirounga leonina ) reveals a conspicuous increase in foraging activity at the standing meander site up to 5 times larger than during the rest of her three-month trip west of the Kerguelen I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 69 publications
3
26
0
Order By: Relevance
“…Other observations of SCMs, not necessarily attributed to diatom SCMs, have shown that Adelie penguins and elephant seals target krill and mesopelagic fish that congregate around SCMs (Dragon et al, 2010;Kahl et al, 2010;Williams et al, 2011;Saijo et al, 2017;Rivière et al, 2019;Siegelman et al, 2019). For elephant seals, this is true both in oceanic regions around the Kerguelen plateau and around the ice-edge.…”
Section: The Ecological Role Of Scms In the Southern Oceanmentioning
confidence: 90%
See 2 more Smart Citations
“…Other observations of SCMs, not necessarily attributed to diatom SCMs, have shown that Adelie penguins and elephant seals target krill and mesopelagic fish that congregate around SCMs (Dragon et al, 2010;Kahl et al, 2010;Williams et al, 2011;Saijo et al, 2017;Rivière et al, 2019;Siegelman et al, 2019). For elephant seals, this is true both in oceanic regions around the Kerguelen plateau and around the ice-edge.…”
Section: The Ecological Role Of Scms In the Southern Oceanmentioning
confidence: 90%
“…Without extensive observations of SCMs, assessments of their impact in Southern Ocean ecology is limited. Regional process studies observed that SCMs contribute to water column primary production (Parslow et al, 2001;Westwood et al, 2011;Tripathy et al, 2014Tripathy et al, , 2015, facilitate large downward carbon export events (Kemp et al, 2000;Llort et al, 2018), are sites of macrofauna foraging (Dragon et al, 2010;Kahl et al, 2010;Williams et al, 2011;Saijo et al, 2017;Rivière et al, 2019;Siegelman et al, 2019) and are sites of intense zooplankton grazing (Atkinson et al, 1992;Froneman and Perissinotto, 1996;Kopczynska et al, 2001;Parslow et al, 2001;Gomi et al, 2010;Rembauville et al, 2016a). The ecological significance of an SCM is enhanced when they also represent a subsurface biomass maximum, or high primary production, or both.…”
Section: The Ecological Role Of Scms In the Southern Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…A limiting case is a mixed layer bounded by a strong pycnocline: submesoscale motions are isolated within the mixed layer and do not penetrate into the interior (Boccaletti et al 2007;Fox-Kemper et al 2008). Discussion of submesoscale dynamics in the literature has largely been confined to mixed layer properties and assumed to be negligible deeper in the water column (Klein et al 2008), although recent studies have challenged this paradigm (Siegelman et al 2019;Yu et al 2019a). In wintertime conditions, however, many regions of the ocean have a weak pycnocline at the base of the mixed layer; in these locations submesoscale instabilities and submesoscale advection have been proposed to extend beyond the depth of a traditionally-defined mixed layer (Erickson and Thompson 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the impact of sub‐mesoscale fronts on upper trophic levels remains largely unknown due to the practical difficulty of simultaneously recording physical and biological data at high resolution. The very few studies addressing this topic with in situ observations revealed that sub‐mesoscale fronts are favorable habitats for several organisms such as zooplankton (Powell and Ohman, ), juvenile tunas (Snyder et al ), and elephant seals (Siegelman et al ), that exploit sub‐mesoscale fronts to enhance their foraging activity. Here we focus on southern elephant seals (SES) living in the ACC; these previous studies suggest that sub‐mesoscale fronts may have an impact on these marine mammals’ behavior.…”
mentioning
confidence: 99%